Cigarette Smoke Increases CD8α+ Dendritic Cells in an Ovalbumin-Induced Airway Inflammation - Brüggemann, Thayse Regina; Fernandes, Paula; Oliveira, Luana de Mendonça; Sato, Maria Notomi; Martins, Mílton de Arruda; Arantes-Costa, Fernanda Magalhães (Frontiers in Immunology, 2017)
Asthma is an allergic lung disease and when associated to cigarette smoke exposition, some patients show controversial signs about lung function and other inflammatory mediators. Epidemiologic and experimental studies have shown both increasing and decreasing inflammation in lungs of subjects with asthma and exposed to cigarette smoke. Therefore, in this study we analysed how cigarette smoke affects pro-inflammatory and anti-inflammatory mediators in a murine model of allergic pulmonary inflammation. We sensitized Balb/c mice to ovalbumin (OVA) with two intraperitoneal injections. After sensitization, the animals were exposed to cigarette smoke twice a day, 30 minutes per exposition, for twelve consecutive days. In order to drive the cell to the lungs, four aerosol challenges were performed every 48 hours with the same allergen of sensitization. OVA sensitization and challenge developed pulmonary Th2 characteristic response with increased airway responsiveness, remodelling, increased levels of IgE, IL-4 and IL-13. Cigarette smoke, unexpectedly, reduced the levels of IL-4 and IL-13 and simultaneously decreased anti-inflammatory cytokines as IL-10 and TGF-β in sensitized and challenged animals. OVA combined with cigarette smoke exposition decreased the number of eosinophils in BAL and increased the number of neutrophils in lung. The combination of cigarette smoke and lung allergy increased recruitment of lymphoid dendritic cells into lymph nodes, which may be the leading cause to an increase in number and activation of CD8+ T cells in lungs. In addition, lung allergy and cigarette smoke exposure decreased an important regulatory subtype of dendritic cell such as plasmacytoid dendritic cell as well as its activation by expression of CD86, PDL2 and ICOSL, and it was sufficient to decrease T regs influx and anti-inflammatory cytokines release such as IL-10 and TGF-β but not enough to diminish the structural changes. In conclusion, we observed in this model that OVA sensitization and challenge combined with cigarette smoke exposure leads to mischaracterization of the Th2 response of asthma by decreasing the number of eosinophils, IL-4 and IL-13 and increasing number of neutrophils, which is related to the increased number of CD8ɑ+ DCs and CD8+ T cells as well as reduction of the regulatory cells and its released cytokines.